2018
DOI: 10.22159/ajpcr.2018.v11i5.23103
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Bioactive Components of Caralluma Umbellata Haw. (Apocynaceae) by Gas Chromatography and Mass Spectroscopy Analysis

Abstract: Objective: The aim of this study was to carry out Gas Chromatography and Mass Spectroscopy (GC–MS) studies and to determine the bioactive compounds of Caralluma umbellata whole plant extract.Methods: Whole plant of C. umbellata was cleaned, shade dried, and pulverized to powder in a mechanical grinder. Required quantity of powder sample was weighed and transferred to stoppered flask separately and treated with ethanol until the powder is fully immersed. The flask was shaken every hour for the first 6 h and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Azafrin (C 27 H 38 O 4 ) derivates from tetraterpenoids (C 40 ). It has been found in many medicinal plants such as rhizome of Alectra chitrakutensis , Bergenia ciliate , Caralluma umbellate , and Alectra parasitica , and it has the functions of being antimicrobial, anti-inflammatory, analgesic, antioxidant, treatment of cardiovascular diseases [90,91,92,93]. Roots of C. grandiflora Benth display orange-yellow color, which is largely due to the presence of abundant azafrin as A. parasitica [93].…”
Section: Discussionmentioning
confidence: 99%
“…Azafrin (C 27 H 38 O 4 ) derivates from tetraterpenoids (C 40 ). It has been found in many medicinal plants such as rhizome of Alectra chitrakutensis , Bergenia ciliate , Caralluma umbellate , and Alectra parasitica , and it has the functions of being antimicrobial, anti-inflammatory, analgesic, antioxidant, treatment of cardiovascular diseases [90,91,92,93]. Roots of C. grandiflora Benth display orange-yellow color, which is largely due to the presence of abundant azafrin as A. parasitica [93].…”
Section: Discussionmentioning
confidence: 99%
“…Such watersoluble pigment was tentatively proposed to be azafrin, a C27 apocarotenoid (Kuhn, 1935;Eschenmoser & Eugster, 1975). Azafrin, which exhibits antioxidant and cardioprotective properties (Yang et al, 2018), is found at high levels in particular organs of other parasitic plants, including the roots of Centranthera grandiflora and the rhizomes of Alectra parasitica, but also in non-parasitic medicinal plants such as Caralluma umbellata (Agrawal et al, 2014;Evanjaline & Vr, 2018;Verma et al, 2019;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The most promising approach in therapy is the use of natural substances with cytotoxic activity concerning tumor cells but not affecting healthy ones. Such substances include lupane triterpenoids-betulin, betulinic and betulonic acids and their derivatives [1][2][3][4][5][6][7]. Recent studies have shown that the combination of triterpenoids such as oleanolic, ursolic and betulinic acids with 5-fluorouracil might be a useful tool with reduced doses of an anticancer drug-5-fluorouracil and without any side effects.…”
Section: Introductionmentioning
confidence: 99%